184k views
4 votes
Solve 5y'' + 3y' – 2y = 0, y(0) = 0, y'(0) = 2.8 y(t) = 0 Preview

User MoonBun
by
4.9k points

1 Answer

3 votes

Answer: The required solution is


y(t)=-(7)/(3)e^(-t)+(7)/(3)e^{(1)/(5)t}.

Step-by-step explanation: We are given to solve the following differential equation :


5y^(\prime\prime)+3y^\prime-2y=0,~~~~~~~y(0)=0,~~y^\prime(0)=2.8~~~~~~~~~~~~~~~~~~~~~~~~(i)

Let us consider that


y=e^(mt) be an auxiliary solution of equation (i).

Then, we have


y^prime=me^(mt),~~~~~y^(\prime\prime)=m^2e^(mt).

Substituting these values in equation (i), we get


5m^2e^(mt)+3me^(mt)-2e^(mt)=0\\\\\Rightarrow (5m^2+3y-2)e^(mt)=0\\\\\Rightarrow 5m^2+3m-2=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{since }e^(mt)\\eq0]\\\\\Rightarrow 5m^2+5m-2m-2=0\\\\\Rightarrow 5m(m+1)-2(m+1)=0\\\\\Rightarrow (m+1)(5m-1)=0\\\\\Rightarrow m+1=0,~~~~~5m-1=0\\\\\Rightarrow m=-1,~(1)/(5).

So, the general solution of the given equation is


y(t)=Ae^(-t)+Be^{(1)/(5)t}.

Differentiating with respect to t, we get


y^\prime(t)=-Ae^(-t)+(B)/(5)e^{(1)/(5)t}.

According to the given conditions, we have


y(0)=0\\\\\Rightarrow A+B=0\\\\\Rightarrow B=-A~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)

and


y^\prime(0)=2.8\\\\\Rightarrow -A+(B)/(5)=2.8\\\\\Rightarrow -5A+B=14\\\\\Rightarrow -5A-A=14~~~~~~~~~~~~~~~~~~~~~~~~~~~[\textup{Uisng equation (ii)}]\\\\\Rightarrow -6A=14\\\\\Rightarrow A=-(14)/(6)\\\\\Rightarrow A=-(7)/(3).

From equation (ii), we get


B=(7)/(3).

Thus, the required solution is


y(t)=-(7)/(3)e^(-t)+(7)/(3)e^{(1)/(5)t}.

User Wdkrnls
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.